DAMPAK SOSIAL PARIWISATA DI KAMPUNG TURIS PRAWIROTAMAN: SEBUAH KAJIAN LITERATUR - Eko Sugiarto (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
This research is a literature study with the theme of the tourism social impact in a village, namely Prawirotaman Village in Yogyakarta. There are two questions to be answered in this research, those are (1) how the origin of the name Prawirotaman as a